The China equity market and its comovements with major international equity markets - Soo, Audrey Wai Mun (2015)
This paper looks at the background of the two main stock exchanges (Shanghai Stock Exchange and Shenzhen Stock Exchange) in China since they opened up to foreign investors. It also attempts to investigate linear comovements with major equity markets (United States, Japan, United Kingdom, Hong Kong and Singapore). Using daily returns for these indices, the results suggest that there is little or no correlation and comovements exhibited between the Chinese markets and the global financial conditions in the other markets.